Click Here: Books for ICSE Class 10 Board Exams

Question 1: Given  A = \begin{bmatrix}  3 & 0 \\ 0 & 4  \end{bmatrix}  B=\begin{bmatrix}  a & b \\ 0 & c  \end{bmatrix} , and that  AB = A+B , find the value of  a, b \ \ and c .

Answer:

AB = A+B

\begin{bmatrix}  3 & 0 \\ 0 & 4  \end{bmatrix} . \begin{bmatrix}  a & b \\ 0 & c  \end{bmatrix} = \begin{bmatrix}  3 & 0 \\ 0 & 4  \end{bmatrix} + \begin{bmatrix}  a & b \\ 0 & c  \end{bmatrix}

\begin{bmatrix}  3a & 3b \\ 0 & 4c  \end{bmatrix} = \begin{bmatrix}  3+a & b \\ 0 & 4+c  \end{bmatrix}

\Rightarrow 3a = 3+a \ or \ a = \frac{3}{2}

Similarly, 3b=b \Rightarrow b = 0

and 4c = 4+c \ or \ c = \frac{4}{3}

Hence a =\frac{3}{2},  \ b= 0 \ c= \frac{4}{3}

\\

Question 2: If  P = \begin{bmatrix}  1 & 2 \\ 2 & -1  \end{bmatrix} , and  Q=\begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix} , then find:

i)  P^2-Q^2  ii)  (P+Q)(P-Q)

Also find if   P^2-Q^2 = (P+Q)(P-Q)

Answer:

i)  P^2-Q^2

= \begin{bmatrix}  1 & 2 \\ 2 & -1  \end{bmatrix} . \begin{bmatrix}  1 & 2 \\ 2 & -1  \end{bmatrix} - \begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix} . \begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix}

= \begin{bmatrix}  5 & 0 \\ 0 & 5  \end{bmatrix} - \begin{bmatrix}  1 & 0 \\ 4 & 1  \end{bmatrix}

= \begin{bmatrix}  4 & 0 \\ -4 & 4  \end{bmatrix}

ii)  (P+Q)(P-Q)

= (\begin{bmatrix}  1 & 2 \\ 2 & -1  \end{bmatrix} + \begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix})(\begin{bmatrix}  1 & 2 \\ 2 & -1  \end{bmatrix} -\begin{bmatrix}  1 & 0 \\ 2 & 1  \end{bmatrix} )

= \begin{bmatrix}  2 & 2 \\ 4 & 0  \end{bmatrix} . \begin{bmatrix}  0 & 2 \\ 0 & -2  \end{bmatrix}

= \begin{bmatrix}  0 & 0 \\ 0 & 8  \end{bmatrix}

Therefore P^2-Q^2 \neq (P+Q)(P-Q)

\\

Question 3: Given A = \begin{bmatrix}  2 & 1 \\ 4 & 2  \end{bmatrix}  B=\begin{bmatrix}  3 & 4 \\ -1 & -2  \end{bmatrix} and  C=\begin{bmatrix}  -3 & 1 \\ 0 & -2  \end{bmatrix} , find

i) ABC ii) ACB . Find whether ABC = ACB

Answer:

i) ABC

= \begin{bmatrix}  2 & 1 \\ 4 & 2  \end{bmatrix} . \begin{bmatrix}  3 & 4 \\ -1 & -2  \end{bmatrix} . \begin{bmatrix}  -3 & 1 \\ 0 & -2  \end{bmatrix}

= \begin{bmatrix}  5 & 6 \\ 10 & 17  \end{bmatrix}. \begin{bmatrix}  -3 & 1 \\ 0 & -2  \end{bmatrix}

=\begin{bmatrix}  -15 & -7 \\ -30 & -14  \end{bmatrix}

ii) ACB

=\begin{bmatrix}  2 & 1 \\ 4 & 2  \end{bmatrix}. \begin{bmatrix}  -3 & 1 \\ 0 & -2  \end{bmatrix}.\begin{bmatrix}  3 & 4 \\ -1 & -2  \end{bmatrix}

= \begin{bmatrix}  -6 & 0 \\ -12 & 0  \end{bmatrix}.\begin{bmatrix}  3 & 4 \\ -1 & -2  \end{bmatrix} 

= \begin{bmatrix}  -18 & -24 \\ -36 & -48  \end{bmatrix} 

Therefore ABC \neq ACB

\\

Question 4: If A = \begin{bmatrix}  1 & 2 \\ 3 & 4  \end{bmatrix}  B=\begin{bmatrix}  6 & 1 \\ 1 & 1  \end{bmatrix} and  C=\begin{bmatrix}  -2 & -3 \\ 0 & 1  \end{bmatrix} , find i)CA+B  ii)A+CB . Are these equal.

Answer:

i)CA+B

= \begin{bmatrix}  -2 & -3 \\ 0 & 1  \end{bmatrix} . \begin{bmatrix}  1 & 2 \\ 3 & 4  \end{bmatrix}+\begin{bmatrix}  6 & 1 \\ 1 & 1  \end{bmatrix} 

= \begin{bmatrix}  -11 & -16 \\ 3 & 4  \end{bmatrix}+\begin{bmatrix}  6 & 1 \\ 1 & 1  \end{bmatrix} 

= \begin{bmatrix}  -5 & -15 \\ 4 & 5  \end{bmatrix} 

ii) A+CB 

= \begin{bmatrix}  1 & 2 \\ 3 & 4  \end{bmatrix} + \begin{bmatrix}  -2 & -3 \\ 0 & 1  \end{bmatrix}. \begin{bmatrix}  6 & 1 \\ 1 & 1  \end{bmatrix} 

= \begin{bmatrix}  1 & 2 \\ 3 & 4  \end{bmatrix} +\begin{bmatrix}  -15 & -5 \\ 1 & 1  \end{bmatrix} 

= \begin{bmatrix}  -14 & -3 \\ 4 & 4  \end{bmatrix} 

\\

Question 5: If A = \begin{bmatrix}  2 & 1 \\ 1 & 3  \end{bmatrix}  B=\begin{bmatrix}  3 \\ -11  \end{bmatrix} , find matrix X such that AX=B .

Answer:

A_{2 \times 2} \times X_{m \times n} = B_{2 \times 1}

\Rightarrow m = 2 \ and \ n = 1

Let X = \begin{bmatrix}  a \\ b  \end{bmatrix}

AX=B

\begin{bmatrix}  2 & 1 \\ 1 & 3  \end{bmatrix}. \begin{bmatrix}  a \\ b  \end{bmatrix}=\begin{bmatrix}  3 \\ -11  \end{bmatrix}

\begin{bmatrix}  2a+b\\ a+3b  \end{bmatrix}= \begin{bmatrix}  3 \\ -11  \end{bmatrix}

Therefore

2a+b = 3

a+3b=-11

Solving the above two equations a = 4 \ and \ b = -5

\\

Question 6: If A = \begin{bmatrix}  4 & 2 \\ 1 & 1  \end{bmatrix} , find (A-2I)(A-3I)

Answer:

I = \begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix}

(A-2I)(A-3I)

= (\begin{bmatrix}  4 & 2 \\ 1 & 1  \end{bmatrix}-2\begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix})(\begin{bmatrix}  4 & 2 \\ 1 & 1  \end{bmatrix}-3\begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix}) 

= (\begin{bmatrix}  4 & 2 \\ 1 & 1  \end{bmatrix}-\begin{bmatrix}  2 & 0 \\ 0 & 2  \end{bmatrix})(\begin{bmatrix}  4 & 2 \\ 1 & 1  \end{bmatrix}-\begin{bmatrix}  3 & 0 \\ 0 & 3  \end{bmatrix}) 

= \begin{bmatrix}  2& 2 \\ 1 & -1  \end{bmatrix}.\begin{bmatrix}  1 & 2 \\ 1 & -2  \end{bmatrix} 

= \begin{bmatrix}  4 & 0 \\ 0 & 4  \end{bmatrix} 

\\

Question 7: If A = \begin{bmatrix}  2 & 1 &-1 \\ 0 & 1 & -2  \end{bmatrix} , find i) A^t.A ii) A.A^t

Answer:

A = \begin{bmatrix}  2 & 1 &-1 \\ 0 & 1 & -2  \end{bmatrix}

Therefore A^t = \begin{bmatrix}  2 & 0 \\ 1 & 1 \\ -1 & -2 \end{bmatrix}

i) A^t.A

= \begin{bmatrix}  2 & 0 \\ 1 & 1 \\ -1 & -2 \end{bmatrix}.\begin{bmatrix}  2 & 1 &-1 \\ 0 & 1 & -2  \end{bmatrix} 

= \begin{bmatrix}  4& 2 &-2 \\ 2 & 2 & -3 \\ -2 & -3 & 5 \end{bmatrix} 

ii) A.A^t

= \begin{bmatrix}  2 & 1 &-1 \\ 0 & 1 & -2  \end{bmatrix}.\begin{bmatrix}  2 & 0 \\ 1 & 1 \\ -1 & -2 \end{bmatrix} 

= \begin{bmatrix}  6 & 3 \\ 3 & 5 \end{bmatrix} 

\\

Question 8: If M = \begin{bmatrix}  4 & 1 \\ -1 & 2  \end{bmatrix} , show that 6M-M^2=9I ; where I is a 2 \times 2 unit matrix.

Answer:

6M-M^2=9I

LHS= 6 \begin{bmatrix}  4 & 1 \\ -1 & 2  \end{bmatrix}- \begin{bmatrix}  4 & 1 \\ -1 & 2  \end{bmatrix}.\begin{bmatrix}  4 & 1 \\ -1 & 2  \end{bmatrix} 

= \begin{bmatrix}  24 & 4 \\ 6- & 12  \end{bmatrix}-\begin{bmatrix}  15 & 6 \\ -6 & 3  \end{bmatrix} 

= \begin{bmatrix}  9 & 0 \\ 0 & 9  \end{bmatrix} 

= 9 \begin{bmatrix}  1 & 0 \\ 0 & 1  \end{bmatrix} 

= 9I 

LHS = RHS.  Hence proven.

\\

Question 9:  If P = \begin{bmatrix}  2 & 6 \\ 3 & 9  \end{bmatrix}  Q=\begin{bmatrix}  3 & x \\ y & 2  \end{bmatrix} , find x \ and \ y such that PQ=null \ matrix .

Answer:

PQ=null \ matrix

Therefore

\begin{bmatrix}  2 & 6 \\ 3 & 9  \end{bmatrix} .  \begin{bmatrix}  3 & x \\ y & 2  \end{bmatrix}= \begin{bmatrix}  0 & 0 \\ 0& 0  \end{bmatrix} 

\begin{bmatrix}  6+6y & 2x+12 \\ 9+9y & 3x+18  \end{bmatrix} = \begin{bmatrix}  0 & 0 \\ 0& 0  \end{bmatrix} 

Therefore

6+6y=0 \Rightarrow y = -1 

2x+12=0 \Rightarrow x = -6 

Hence x = -6 \ and \ y = -1 

\\

Question 10: Evaluate \begin{bmatrix}  2 \cos {60^o} & -2 \sin{30^o} \\ -\tan{45^o} & \cos{0^o}  \end{bmatrix} \begin{bmatrix}   \cot{45^o} &  \mathrm{cosec{\ 30^0}}  \\ \sec{60^o} & \sin{90^o}  \end{bmatrix}

Answer:

\begin{bmatrix}  2 \cos {60^o} & -2 \sin{30^o} \\ -\tan{45^o} & \cos{0^o}  \end{bmatrix} \begin{bmatrix}   \cot{45^o} &  \mathrm{cosec{\ 30^0}}  \\ \sec{60^o} & \sin{90^o}  \end{bmatrix}

= \begin{bmatrix}  1 & -1\\ -1 & 1  \end{bmatrix}.\begin{bmatrix}  1 & 2 \\ 2 & 1  \end{bmatrix}

= \begin{bmatrix}  -1 & 1\\ 1 & -1  \end{bmatrix}

\\

Question 11: State True or False with reason

Answer:

i) A+B=B+A : True > addition of matrices is commutative

ii) A-B=B-A : False > subtraction of matrices is not commutative

iii) (B.C).A = B.(C.A) : True > Multiplication of matrices is associative

iv) (A+B).C = A.C+B.C : True > Multiplication of matrices is distributive over addition

v) A.(B-C)=A.B-A.C : True > Multiplication of matrices is distributive over subtraction

vi) (A-B).C=A.C-B.C :  True > Multiplication of matrices is distributive over subtraction

vii) A^2-B^2=(A+B)(A-B) : False > Laws of algebra for factorization is not applicable to matrices

viii) (A-B)^2=A^2-2A.B+B^2 : False >  Laws of algebra for factorization is not applicable to matrices

\\

Click Here: Books for ICSE Class 10 Board Exams

Advertisements